Análise espacial das características hidrodinâmicas e do uso e ocupação do solo da bacia experimental do Riacho Guaraíra mediante uso de geotecnologias - Silva, Jorge Flávio Cazé Braga da Costa (2009)
The sedimentation and erosion problems at the hydrographic basin are seen currently as one of the main problems of modern society and consequently of the urban areas and large Brazilian metropolitan regions. The issue of management and water availability in the hydrographic basin must be treated as an Urban Engineering issue, once that it is in charge of the problems related to water management at the urban level. So, the general objective of this research is to study the land use and occupation and hydrodynamic features of the Guaraíra Experimental River Basin through the geotechnology and field experiments based on the Beerkan methodology, that determines the water retention curves in the soil h(q) and the hydraulic conductivity K(q) through five parameters, two of form and three of normalization, the results will be used to run hydrologic simulations through the Kineros2 model. The study showed that the Beerkan method is applicable, however it needs some adjustment so that it can give better results. The Kineros2 model was used to calculate the soil loss in the basin with data from infiltration parameters found with Beerkan, and results show that the basin lost about 50 ton/hec/year, to the period from January of 2003 to May of 2009. The year 2004 was the one which showed the highest production, i.e. 125,1 ton/hec, while 2009 showed the lowest, i.e. 5,2 ton/hec. Finally, the high permeability level of the basin and its susceptibility to erosion reveal the importance of hydrosedimentologic studies, using the given models and field surveys for more infiltration tests.